ANALISIS KEPRAKTISAN MEDIA PEMBELAJARAN BERBASIS ISPRING UNTUK MATA PELAJARAN IPAS DI SEKOLAH DASAR - Siti Muliatul Afifah; Sumadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyse the practicality of iSpring-based interactive learning media in Natural and Social Sciences (IPAS) learning in primary schools. Interactive media is considered an innovative learning solution that can provide a more engaging and meaningful learning experience. This study was conducted using a quantitative descriptive approach. The instrument used was a practicality questionnaire distributed to teachers and students. The results of the data analysis indicate that iSpring media received very high ratings in terms of ease of use, time efficiency, visual appeal, and support for achieving learning objectives. The average practicality percentage reached 99%, categorised as ‘very practical.’ This media was also found to assist teachers in presenting material more clearly and facilitate students' understanding of IPAS learning concepts.